Abundance of syrphid larvae in willow plantations : role of habitat type, prey (Phratora vulgatissima) availability and interactions with other natural enemies - Johansson, Hans (SLU/Dept. of Ecology, 2009)
A large number of hover fly species are as larvae effective predators and often feed on insect pests in plantations. The leaf-beetle Phratora vulgatissima is a common pest in willow plantations and the aim of this study is to study what may affect the presence of hover flies in this system. The quality of the surrounding habitats, prey availability and interactions with other natural enemies are parameters that may explain variances in densities of hover flies and was here investigated at five localities whereas a total of 40 plots of 5 x 5 meters have been studied in detail. The heteropterans Anthocoris nemorum and Orthotylus marginalis are two natural enemies to P. vulgatissima and whose foraging behaviour differs and their interactions with the hover fly may therefore differ. The syrphid larva and the mirid display a similar foraging behaviour and interactions, e.g. competition and predation, between these two species are thus likely to occur. Experiments were performed in the laboratory to study if there were any differences in proportion of consumed syrphid eggs and in time to consumption of eggs between anthocorids and mirids. The results showed that all plots in field where syrphid eggs were found were surrounded by a high proportion of forest while no eggs were found in plots next to arable land. Leaf beetle egg clutches with syrphid eggs were in average larger in size compared with clutches without. The variation in density of leaf beetle eggs was small between localities and plots, which could explain the lack of association between high densities and abundance of syrphid eggs. The abundance of other enemies, e.g. heteropterans, seemed to have a negative effect on the hover fly since no hover fly eggs were found in plots with high densities of other enemies. Both species of heteropterans consumed a large proportion of syrphid eggs. Contrary to my expectations none of the species had a larger negative impact on the survival of the syrphid neither when considering time to consumption of the egg nor the proportion of consumed syrphid eggs. This study shows that a higher diversity within the enemy-complex may have negative effects on the biological control of pests and that predators within the same guild are susceptible to predation in certain developmental stages. Hover flies are probably of little importance in the biocontrol of leaf beetles in situations with high densities of other natural enemies but have the potential to be particularly important as predators in recently harvested plantations i.e. plantations with low densities of heteropterans.